Mendekonstruksi Pemasaran Konvensional: Studi Fenomenologi Strategi Anti-Marketing Berbasis Nilai Islami pada Warung Jendil Mbah Yamah Talun Blitar - Jeka Widiatmanta; Rima Dewi Oryza Sativa (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This research presents a phenomenological inquiry aimed at deconstructing the conventional marketing paradigm and offering a deeper understanding of alternative practices. It specifically explores the anti-marketing strategy grounded in Islamic values as implemented at Warung Jendil Mbah Yamah, a traditional micro, small, and medium enterprise (MSME) located in Blitar, East Java. Employing a qualitative approach combined with a phenomenological method, the study gathered rich and nuanced data through several techniques, including in-depth interviews with nine carefully selected informants, participatory observation over an extended period, and systematic documentation studies. The thematic data analysis conducted by the researchers revealed that the warung’s anti-marketing strategy rests firmly on three interconnected pillars: (1) a strong reliance on organic word-of-mouth  communication rather than paid advertising, (2) the deliberate creation of an authentic, personal, and inclusive customer experience that builds emotional bonds with visitors, and (3) the consistent integration of Islamic ethical values into every aspect of business operations. These findings provide a meaningful theoretical contribution by synthesizing the concepts of anti-marketing and Islamic entrepreneurship into a new model of “authentic marketing,” where ethical and spiritual values serve as the strategic foundation for long-term sustainability. In practical terms, the results offer guidance for the broader development of MSMEs in Indonesia, showing that authenticity, ethical commitment, and adherence to core values can represent a stronger and more sustainable competitive advantage than conventional promotional strategies.